2011
DOI: 10.1016/j.juro.2011.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inflammatory Related Gene Expression in Clear Cell Renal Cell Carcinoma Development and Clinical Outcomes

Abstract: Purpose Renal cell carcinoma is the eighth most common cancer in the United States and clear cell renal carcinoma is the most common type. Many signaling pathways are implicated in clear cell renal carcinoma development, including the inflammation pathway. However, less is known about how gene expression variation in this pathway influences clear cell renal carcinoma development and clinical outcomes. Materials and Methods Gene expression in tumor and adjacent normal tissues from 93 patients was detected usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…[10][11][12] Visceral obesity increases cancer risk and promotes tumor progression through its adverse impact on inflammation and metabolism, and upregulation of genes involved in tumor cell invasion and metastasis. 3,6,18 Furthermore, the prevalence of abdominal obesity has recently increased in Asian countries because of a Westernized diet. Therefore, the necessity for precise and clinically expedient measures for quantifying visceral obesity is evident.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Visceral obesity increases cancer risk and promotes tumor progression through its adverse impact on inflammation and metabolism, and upregulation of genes involved in tumor cell invasion and metastasis. 3,6,18 Furthermore, the prevalence of abdominal obesity has recently increased in Asian countries because of a Westernized diet. Therefore, the necessity for precise and clinically expedient measures for quantifying visceral obesity is evident.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a panel of inflammation related genes has recently been analyzed in ccRCC by Tan and colleagues and related to risk of recurrence ( GADD45G ) and death ( CARD9, CIITA and NCF2 ) [15]. Only one report highlights the role of Toll-like receptors (TLRs) in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-inducible factors (HIF) pathway and compensatory hyperactivation of angiogenesis through upregulation of VEGFR and PDGFR pathways are thought to be particularly important in ccRCC pathogenesis, given the highly vascularised nature of renal tumours and the specific association with mutations in VHL [9]. In addition, activation of PI3K/AKT/mTOR [10], Wnt/β-catenin [4], [11], epithelial to mesenchymal transition (EMT) [12], [13], HGF/MET [11], [14] as well as inflammatory [15] pathways have all been reported to be implicated in RCC carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, gene expression studies in large cohorts of RCC-bearing patients have suggested that some molecules such as IL-1, IL-6, TNF-α, C1q, and C1r could be implicated in the initiation and promotion of an intratumor inflammatory cascade (Peri, Devarajan, Yang, Knudson, & Balachandran, 2013;Romero et al, 2006;Tan et al, 2011). The RCC tumor cells probably orchestrate this inflammatory environment as suggested by the presence of several cytokines in the supernatant of RCC primary cultures, including IL-8, IL-10, TGF-β, GM-CSF, TNF-α, and VEGF (Gogusev, Augusti, Chrétien, & Droz, 1993;Knoefel et al, 1997;Lahn et al, 1999;Lee, Chun, Nadiminty, Lou, & Gao, 2007;Sievers et al, 2007).…”
Section: The Ccrcc Tumor Microenvironmentmentioning
confidence: 99%
“…Thus, the plasma concentration of C-reactive protein in RCC-bearing patients (Hu et al, 2014;Ito et al, 2006;Jagdev et al, 2010;Karakiewicz et al, 2007;Lamb, McMillan, Ramsey, & Aitchison, 2006;Steffens et al, 2012) and the presence of an inflammatory gene signature in RCC (Romero et al, 2006;Tan et al, 2011) are linked to a higher tumor grade and positive metastatic status at diagnosis and poor prognosis. In addition, other inflammatory markers are related to poor survival in RCCbearing patients, including an augmented erythrocyte sedimentation rate, leukocytosis, thrombocytosis, and the increased plasmatic concentrations of IL-6 and TNF-α (Dosquet, Coudert, Lepage, Cabane, & Richard, 1997;Dosquet et al, 1994;Escudier et al, 2014;Fox et al, 2013;Negrier et al, 2004;Pichler et al, 2013;Wu et al, 2011;Yoshida et al, 2002).…”
Section: The Ccrcc Tumor Microenvironmentmentioning
confidence: 99%